2008
DOI: 10.5539/elt.v1n1p34
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Online Collaboration in Promoting ESL Writing

Abstract: The study examined an ESL writing class, which consisted of 36 students, at a community college of Hong Kong. The students took part in three online collaborative writing tasks by sending drafts to peers who gave them suggestions and comments for improvement and working together on the completion of the writing tasks via email.The 36 students worked in small groups of four to six. They wrote, responded and revised using the email system offered by the WebCT interface of their course book. The results were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…This finding conforms the findings of previous studies (e.g. Berbache, 2007;Choi, 2008;Kessler, 2009;Hadjerrouit 2011;Woo et al, 2011;Razak & Saeed, 2014a) that learners made such additions to incorporate additional information to their writing. It also helped them to correct the errors in grammar and mechanisms (Horne, 2011;Yang, 2010).…”
Section: What Types Of Revision Changes Did the Efl Arab Learners Maksupporting
confidence: 83%
See 2 more Smart Citations
“…This finding conforms the findings of previous studies (e.g. Berbache, 2007;Choi, 2008;Kessler, 2009;Hadjerrouit 2011;Woo et al, 2011;Razak & Saeed, 2014a) that learners made such additions to incorporate additional information to their writing. It also helped them to correct the errors in grammar and mechanisms (Horne, 2011;Yang, 2010).…”
Section: What Types Of Revision Changes Did the Efl Arab Learners Maksupporting
confidence: 83%
“…For instance, Choi (2008) and Kessler (2009) reported that learners focused on how to make the meaning clearer in their revised texts, thus, attending to fluency rather than accuracy. Other studies reported that learners focused on conclusion and sentences or ideas relative to the text in their final drafts (Arnold et al, 2009;Yang, 2010), content (Hadjerrouit, 2011), organization and cohesion (Alshumaimeri et al, 2011) and more language related contributions (LRCs) than non-language related contributions (NLRCs Kessler et al, 2012).…”
Section: Previous Research On Peer Writing Revisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have established the usefulness of PBL and online collaborative learning in countries such as the USA (Changwatchai, 2006), Hong Kong (Choi, 2008), Thailand (Simpson, 2011), and Oman (Al Kindy, 2007;Al-Abri, 2009). Changwatchai (2006) collaboration in The University of Texas at Austin.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The researcher stated that students should be informed about the desired behaviors before the semester starts in order to reduce students' frustration. Choi (2008) also investigated students' feelings and attitudes towards the use of online collaboration in English as a second Language (ESL) writing. The sample of the study consisted of a class with 36 higher diploma (intermediate level) students from a community college in Hong Kong.…”
Section: Review Of Literaturementioning
confidence: 99%